2018
DOI: 10.3906/bot-1703-58
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric analysis of airborne pollen grains in the city of Uşak, Turkey

Abstract: IntroductionAllergic diseases affect 20%-30% of Turkish population and constitute an important disease group due to the labor and financial losses they cause (Bıçakçı et al., 2009). In some countries, the rates of diseases causing allergy in humans are as follows: 14% in Finland, 5.9%-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
2
4
0
1
Order By: Relevance
“…The time period (e.g., month) in which highest pollen detection was obtained and some of the dominant taxa recorded in Gümüşhane (Pinaceae, Cupressaceae/ Taxaceae, Quercus, Betula, and Poaceae) were similar to those obtained for such studies done in Turkey (İnceoğlu et al, 1994;Güvensen and Öztürk, 2003;Ayvaz et al, 2008;Çeter et al, 2012;Uğuz et al, 2017Uğuz et al, , 2018. In particular, the month of highest concentration and the most dominant taxa were similar to those found in a study conducted in Kastamonu (Çeter et al, 2012).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The time period (e.g., month) in which highest pollen detection was obtained and some of the dominant taxa recorded in Gümüşhane (Pinaceae, Cupressaceae/ Taxaceae, Quercus, Betula, and Poaceae) were similar to those obtained for such studies done in Turkey (İnceoğlu et al, 1994;Güvensen and Öztürk, 2003;Ayvaz et al, 2008;Çeter et al, 2012;Uğuz et al, 2017Uğuz et al, , 2018. In particular, the month of highest concentration and the most dominant taxa were similar to those found in a study conducted in Kastamonu (Çeter et al, 2012).…”
Section: Discussionsupporting
confidence: 79%
“…atmospheric pollen concentration of many cities in Turkey (İnce, 1994;İnceoğlu et al, 1994;Pehlivan and Butev, 1994;Öztürk, 2002, 2003;Ayvaz et al, 2008;Tosunoğlu et al, 2015aTosunoğlu et al, , 2015bBıçakçı et al, 2017;Uğuz et al, 2017Uğuz et al, , 2018 and also in other countries (Nilsson et al, 1977;Goldberg et al, 1988;Subiza et al, 1995;Abreu et al, 2003;Boral et al, 2004;Docampo et al, 2007).…”
mentioning
confidence: 99%
“…Regarding the pollen season, Alnus and Fraxinus are arboreal species that flower in winter whereas Betula, Olea and Platanus with spring flowering. Several studies reported similar findings for Alnus in the same area and for other countries regarding the start, end date and duration of the MPS, but with differences in the total amount of annual pollen [10,49,50]. Some authors found that meteorological parameters, as mean temperature during the previous months to pollination, affect the annual airborne pollen sum [51].…”
Section: Discussionmentioning
confidence: 69%
“…Bu nedenle farklı bölgelere ait atmosferik polen verileri klinisyenler ve alerji hastalarının saman nezlesi semptomlarını çok daha iyi yönetebilmeleri açısından önem taşımaktadır [2]. Bununla beraber atmosferdeki polen konsantrasyonunun meteorolojik değişimlerden büyük ölçüde etkilendiği bilinmektedir [3,4] ve tüm dünyada olduğu gibi Türkiye'nin de farklı bölgelerinde değişik yöntemler kullanılarak yapılan çok sayıdaki aeropalinolojik çalışmada, atmosferik polenlerin tespit edilmesi ve meteorolojik faktörlerle ilişkileri açısından önemli veriler elde edilmiştir [5][6][7][8][9][10]. Aeropalinolojik çalışmalarda tanımlanan polenler genellikle ağaç, çayır ve yabani otsular olmak üzere üç grupta incelenmektedir.…”
Section: Introductionunclassified